2005
DOI: 10.1021/la047207g
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvent Effects on the Stability of Catanionic Vesicles Formed from Ion-Pair Amphiphiles

Abstract: Four ion-pair amphiphiles (IPAs), derived from the pairing of alkyltrimethylammonium chlorides and sodium alkyl sulfates, were used to form catanionic vesicles in water upon the mechanical dispersion method. For the first time in the literature, short-chained alcohols (methanol, ethanol, 1-propanol, and 1-butanol) were added as cosolvents at a variety of concentrations and systematically studied for their effects on the stability of the ensuing vesicles. Dynamic light scattering measurements indicated that ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…Thus, the presence of nonaqueous polar solvents effectively induced catanionic vesicle formation from catanionic precipitates. This finding was extended to the formation of catanionic vesicles from IPAs as well 14,27 . In addition, Huang s group revealed that the catanionic vesicles fabricated from bolaamphiphiles or gemini surfactants and oppositely charged surfactants possessed superior thermo-stability in aqueous solutions.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Thus, the presence of nonaqueous polar solvents effectively induced catanionic vesicle formation from catanionic precipitates. This finding was extended to the formation of catanionic vesicles from IPAs as well 14,27 . In addition, Huang s group revealed that the catanionic vesicles fabricated from bolaamphiphiles or gemini surfactants and oppositely charged surfactants possessed superior thermo-stability in aqueous solutions.…”
Section: Introductionmentioning
confidence: 69%
“…Catanionic vesicles prepared from pure aqueous-phase IPAs usually exhibit short-term physical stability 8,12,14 . To overcome this shortcoming, various approaches have been employed to adjust the inter-vesicle and/or intra-vesicle interactions and thereby enhance the catanionic vesicles physical stability.…”
Section: Ipasmentioning
confidence: 99%
See 3 more Smart Citations